DEER FAUNA FROM THE AULLA QUARRY (VAL DI MAGRA, NORTHERN APENNINES). BIOCHRONOLOGICAL REMARKS (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1995)
The occurrence in the continental deposits of Aulla quarry of deer characteristic of Early Villafranchian fauna, referred to Procapreolus cusanus and Pseudodama ex gr. pardinensis-lyra, is reported. These finds make questionable the correlation of the sedimentary succession to the Early Pliocene, based on the pollen assemblage.
Keywords: Mammalia; Cervidae; Early Villafranchian; Late Pliocene; Italy.